Metode Fuzzy TOPSIS Sebagai Sistem Pendukung Keputusan dalam Menentukan Pegawai Berprestasi - Izdhihar, Fairuz Nadhif; Alisah, Evawati; Abdussakir, Abdussakir (Jurnal Riset Mahasiswa Matematika, 2023)
Fuzzy TOPSIS as a decision support system is a mathematical method with the best alternative concept chosen not only to have the shortest distance to the positive ideal solution, but also to have the longest distance to the negative ideal solution. The use of Fuzzy TOPSIS as a decision support system can minimize the weaknesses that exist in the TOPSIS method. The purpose of this study is to apply the Fuzzy TOPSIS method as a Decision Support System (SPK) to determine outstanding employees at the Batu City Population and Civil Registration Office. The Human Resources (HR) Division has the task of validating the value and processing the value of employee work goals and work behavior using the Fuzzy TOPSIS implementing into recommendations for outstanding employees. Data processing is carried out fuzzy, while calculations are carried out by the TOPSIS method. The output of this calculation is in the form of ranking the value of preferences and recommendations available for all employees. The calculation results obtained the highest preference value, namely by the first alternative with a value of 1. The alternative occupied a position as an outstanding employee at the Batu City Population and Civil Registration Office.